Global justice and childhood: introduction. Issue 3 (2nd September 2019) - Drerup, Johannes; Schweiger, Gottfried
ABSTRACT: This brief introduction frames a guest-edited collection of eleven contributed articles in the Journal of Global Ethics focused on global justice and childhood. On a general level, there is widespread consensus that there is a strong need for improvement in the lives of children around the globe. What global justice demands in this regard, however, has never been fleshed out in detail and there is only a little philosophical literature on this topic. Against this background, five aspects of the question of global justice for children need to be addressed. First, one has to take into account the debate between cosmopolitanism and particularism, as well as the debate as to whether and to what extent individual, collective or institutional actors should be prioritized. Secondly, a theory of global justice for children must explain how the content of global justice for children is founded and justified, and what it comprises. Third, different principles can be used to assess global justice for children. Only two prominent alternatives are mentioned here: egalitarianism and sufficiency. Fourthly, the temporal dimension of global justice is of particular importance for children. Fifthly, an approach focusing on the examination of injustices is equally necessary.